EFL Teachers' Attitudes towards Self-Directed Language Learning in Diverse Academic Settings - Seyyed Hossein Kashef; Fatemeh Barzegari (International Journal of Practical and Pedagogical Issues in English Education)
The current research gathered and compared Iranian instructors' perspectives regarding self-directed language learning in a variety of academic contexts including language institutes, schools and universities. To do the study, 120 EFL teachers with BA, MA, or PhD degrees between the ages of 23 and 54 from Urmia, West Azarbaijan, were chosen to participate in this study. The researcher adopted a teacher questionnaire from the questionnaire used by Borg and Al-Busaidi (2012) and Camilleri (1999). Based on the findings of current study, it was concluded that most of Iranian EFL teachers have positive and favorable attitudes toward self-directed learning and its different constructs. They mostly even in different educational settings positively stated that learners needed to form specific habits such as studying in library, being provided with opportunities for completing tasks alone and moving education to out of classroom. The extent to which teacher in different settings agreed to them was not statistically different. The results of the current study can help teacher trainers to integrate the self-directed learning into their educational curriculum to encourage teachers to use and implement it.